Rusya-Ukrayna Savaşında Yaptırımlar ve Enerji Güvenliği; Karşılıklı Ekonomik Bağımlılıklar Perspektifinden Bir Değerlendirme(Sanctions and Energy Security in the Russia-Ukraine War; An Evaluation from the Perspective of Mutual Economic Dependencies) - Orhan BATTIR; Levent YİĞİTTEPE (Yönetim ve Ekonomi, 2023)
The Russia-Ukraine War, which started with hot conflicts in February 2022, has brought the EU countries face to face with more serious problems than ever in the recent past, especially in terms of energy supply security. It is difficult to say that European countries, which tend to react to Russia's attack on Ukraine under the protection of the EU on the one hand and NATO on the other, through sanctions, have shown the expected effect, especially due to their dependence on Russian natural gas. Although the EU has resorted to alternative energy supply methods to get rid of the energy crisis it has fallen into, this is far from being an effective solution in the short term, as it requires new and seriously high-cost investments.. Therefore, no EU country can afford to adopt a strict stance that could mean ending its relations with Russia. In this study, evaluations on the energy supply security problem caused by the Russia-Ukraine War in EU countries and, accordingly, the future of EU-Russia relations in the short and medium term are included.